2020
DOI: 10.1051/0004-6361/201937183
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter wave spectroscopy of cyanoketene (NC–CH=C=O) and an observational search in the ISM

Abstract: Context. Ketene was detected in the interstellar medium (ISM) in 1977. Until now, only one derivative, the ketenyl radical, has been observed in this medium. Due to its large dipole moment value, cynaoketene is one of the best candidates for possible ketene derivative detection. Aims. To date, the measurements of the rotational spectra have been limited to 60 GHz. The extrapolation of the prediction in the millimeter wave domain is inaccurate and does not permit an unambiguous detection. Methods. The rotationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Indeed, the 3CFH + strongest line is about ve times stronger than the 2CFH + strongest line. For instance, the 3CFH + line 13 1 2 MHz. In other words, one may nd that the rotational spectrum for 2CFH + is less intense than that for 3CFH + .…”
Section: Rotational Parameters Of 2cfh + and 3cfh +mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the 3CFH + strongest line is about ve times stronger than the 2CFH + strongest line. For instance, the 3CFH + line 13 1 2 MHz. In other words, one may nd that the rotational spectrum for 2CFH + is less intense than that for 3CFH + .…”
Section: Rotational Parameters Of 2cfh + and 3cfh +mentioning
confidence: 99%
“…Despite unfavourable conditions to the chemical formation in the interstellar medium (ISM), 1,2 more than a third of already detected molecules (more than 200 molecular species 3 ) is made of complex organic molecules (COMs). 4 In interstellar clouds and associated circumstellar envelopes of the asymptotic giant branch (AGB) stars, molecules with an order of magnitude of atom number ranging from 2 to 13 atoms in the gas phase have been discovered by high-resolution spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…For each source, because these are nondetections, we have had to make assumptions about the physical conditions in which thioacetaldehyde might be found. For all sources considered in this subsection, these parameters were chosen to match those used in a similar analysis of cyanoketene [40] (since many of these sources do not have acetaldehyde detections in them). These parameters and the literature sources they were obtained from are provided in Table 4.…”
Section: Search Using Astrochemical Surveys At Iram Large Programmentioning
confidence: 99%
“…The microwave spectrum showed evidence of hindered internal rotation [13] and it was detailed a few years later together with a study of eight isotopic variants of thioacetaldehyde [14]. The measurements were done up to 40 GHz and transitions up to J = 35 in the ground torsional state were assigned [14]. Information on dipole moment as well as methyl top internal rotation barrier heights was also obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Ketene itself was detected toward Sgr B2 (Turner 1977) and other regions (Turner et al 2020). Ketenyl radical was observed toward the starless core Lupus-1A and the molecular cloud L483 by Agúndez et al (2015) while cyanoketene has not yet been detected (Margulès et al 2020). Propadienone has also eluded detection so far (Loomis et al 2015;Loison et al 2016;Shingledecker et al 2019), despite its two higher-energy isomers propynal (HCCCHO; Irvine et al 1988) and cyclopropenone (c-C 3 H 2 O; Hollis et al 2006) being found.…”
Section: Introductionmentioning
confidence: 99%